Recognition and response: policing ‘Forced marriage’ in England - Miles-Johnson, Toby (Policing and society, 2021)
Forced marriage occurs when an individual is pressured psychologically or physically into marriage. Methods to detect forced marriage are challenging for most police organisations, who are prevented from intervening due to honour-systems and cultural values; as well as ensuing physical and psychological barriers, which prevent victim reporting. Applying key components of Sellin’s (1933) Culture Conflict theory, 21 semi-structured interviews were conducted with police officers and forced marriage specialists to determine whether police are able to recognise and respond to forced marriage situations, and whether lack of awareness, understanding and training on forced marriage influences officers’ perceptions of policing of forced marriage. The findings from this study suggest that police officers are not cognisant of forced marriage and are not trained adequately in it so that awareness of forced marriage and the cultural conflict it creates forms part of their habitual investigative processes.